Batik Stamp Canting as An Interior Material - Harmilyanti Sulistyani; Raden Ersnathan Budi Prasetyo; Indaro Indarto (Institut Seni Indonesia Surakarta, 2022)
Batik’s recognition as a world heritage by UNESCO has given a positive impetus to the batik industry. The encouragement, however, has yet to reach the batik canting cap (stamp) home industry, which is a supporting sector of stamped batik. Knowledge and expertise in making canting stamps are difficult to transfer to the next generation because the economic value is not promising. The raw material of the canting stamp, namely copper metal, has unique characteristics. In terms of visual appearance, the canting stamp has an aesthetic value for the interior. An experimental method is used in the research to produce interior material prototypes that are suitable for market conditions. The making of an interior elements model as a prototype reference uses computer programs and tools for design, which are known as computer-aided design (CAD) to reduce costs because it can provide a photorealistic visualization. The outcome is expected to encourage the growth of the canting stamp batik home industry, hence its economic value will increase. The ultimate goal is to increase employment by pushing canting stamp batik quantity production due to the demand for interior materials then will open up opportunities to regenerate the skills to make canting stamp batik.